Finance - Cornett, Marcia Millon (McGraw-Hill/Irwin, 2009)
While developing Finance: Applications & Theory, McGraw-Hill engaged professors in a number of activities to better understand the goals, challenges, and successes involved in teaching the Undergraduate Corporate Finance course. We connected with more than 600 corporate finance instructors through reviews, focus groups, class tests, and course surveys. You spoke; we listened; and the result is a market-driven corporate finance book that will help students succeed in the classroom and in their careers